Work engagement interventions can be effective: a systematic review - Knight, Caroline; Patterson, M.; Dawson, J. (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2019)
© 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group. Work engagement is associated with important individual and organisational outcomes (e.g. employee health and well-being, performance). This narrative systematic review aims to synthesise the increasing number of work engagement interventions and inform future research by exploring: (1) the specific intervention foci, delivery methods and content of engagement interventions; (2) intervention effectiveness; and (3) underlying mediators and moderators. A systematic search for interventions employing a validated engagement measure revealed 40 studies. Five were personal resource building, twelve job resource building, three leadership training, eighteen health promotion, and two job and personal resource building. Twenty (50%) studies observed significant positive effects on work engagement, two (5%) had a negative effect, and eighteen (45%) had no effect. Job and personal resources, job demands and well-being were important mediators. Moderators included the specific intervention focus and delivery method, employee participation, manager support, and intervention level (top-down vs bottom-up). Bottom-up interventions, and job crafting and mindfulness interventions particularly, were most successful. Implementation difficulties were common, including poor response and attrition rates, and adverse factors (e.g. organisational restructuring, redundancy, economic downturn). We highlight implications for research and practice and stress the need to test underlying theories to build knowledge around how, why, and when interventions work.